EFFECT OF GRAMMAR LEARNING STRATEGIES (GLS) IN LANGUAGE LEARNING: CASE STUDY ON VOCATIONAL HIGH SCHOOL STUDENTS IN DETERMINING PROFICIENCY LEVELS - Aisyah Aisyah; Ferri Hidayad; Muhammad Bambang Purwanto (Wiralodra English Journal, 2024)
The current study looked into the grammar learning techniques (GLS) employed by SMK Negeri 6 Palembang students. In particular, it looked at the mean variations in the GLS dependent on the students' competence levels. The data was gathered through a survey-based quantitative research design. Undergraduate grammar course students at SMK Negeri 6 Palembang were randomly given a set of surveys via Google Forms. Forty students answered the questionnaire, making them research participants. To evaluate the data, both descriptive and inferential analysis were performed. The results showed that the most frequently employed cognitive, metacognitive, affective, and social strategies were, in that order, taking notes while listening to their teacher's explanations, figuring out why they made mistakes, pushing themselves to practice grammar, and asking friends for assistance. It was discovered that students most frequently employed social strategy. The study also showed that more high proficient students than low proficient students employed all strategies. For future research, teachers might adapt their teaching strategy to align with students' grammar learning strategies by using the research findings. Less skilled students can also pick up the strategy employed by the more skilled students, allowing them to gain from using the strategies in their own learning grammar.